Frequency of de novo variants and parental mosaicism in families with inactivating PTH/PTHrP signaling disorder type 2 - Vado, Yerai; Pereda, Arrate; Manero-Azua, Africa, Spanish Network for Imprinting Disorders; Perez de Nanclares, Guiomar (Frontiers in Endocrinology, 2023)
Objective: iPPSD2 is a rare inherited autosomal dominant endocrine disorder caused by inactivating GNAS pathogenic variants. A high percentage of de novo cases has been suggested. Part of it could be due to parental mosaicism, but its frequency is unknown. Design: A retrospective study including a series of 95 genetically confirmed iPPSD2 probands. Methods: The frequency of de novo cases was evaluated and the distribution of the type of variants was compared according to the type of inheritance. The putative involved allele was determined by RT-PCR or ASO-PCR. The GNAS mosaicism was studied by deep targeted next-generation sequencing (NGS) from the corresponding parental DNA. Results: In 41 patients the variant was of de novo origin and in 24 the origin could not be established. In both cases 66.67% of variants generated a truncated or absent protein whereas the rest of the variants were missense or in-frame deletion/duplication. Parental origin was studied in 45 of those patients and determined in 35. Curiously, the percentage of variants at the paternal allele was higher than when paternally inherited (31.1 % vs 6.67 %). NGS detected mosaicism in three independent families: one from paternal DNA (allelic ratio 10%) and two from maternal DNA (allelic ratio 10% and 2%). Conclusion: iPPSD2 is characterized by a high frequency of de novo pathogenic variants. Parental mosaicism is rare (8.11%) but should be systematically searched with targeted NGS, taking into account its importance in genetic counselling.